Solar-to-Hydrogen Production at 14.2% Efficiency with Silicon Photovoltaics and Earth-Abundant Electrocatalysts. Issue 10 (13th August 2016) - Schüttauf, Jan-Willem; Modestino, Miguel A.; Chinello, Enrico; Lambelet, David; Delfino, Antonio; Dominé, Didier; Faes, Antonin; Despeisse, Matthieu; Bailat, Julien; Psaltis, Demetri; Moser, Christophe; Ballif, Christophe
Abstract : Affordable, stable and earth-abundant photo-electrochemical materials are indispensable for the large-scale implementation of sunlight-driven hydrogen production. Here we present an intrinsically stable and scalable solar water splitting device that is fully based on earth-abundant materials, with a solar-to-hydrogen conversion efficiency of 14.2%. This unprecedented efficiency is achieved by integrating a module of three interconnected silicon heterojunction solar cells that operates at an appropriate voltage to directly power microstructured Ni electrocatalysts. Nearly identical performance levels were also achieved using a customized state-of-the-art proton exchange membrane (PEM) electrolyzer. As silicon heterojunction solar cells and PEM electrolysis systems are commercially viable, easily scalable and have long lifetimes, the devices demonstrated in this report can open a fast avenue toward the industrialization and deployment of cost effective solar-fuel production systems.